miR-23a-3p inhibits sepsis-induced kidney epithelial cell injury by suppressing Wnt/β-catenin signaling by targeting wnt5a - Ye,Junwei (2022)
The present study was designed to investigate the involvement of miR-23a-3p in the progression of sepsis-induced acute kidney injury (AKI). The expression levels of miR-23a-3p and wnt5a in sepsis-induced AKI patients and lipopolysaccharide (LPS)-treated HK-2 cells were detected by real-time PCR and western blotting. Then, the effects of miR-23a-3p overexpression on cell viability, apoptosis, and inflammatory cytokines secretion in LPS-stimulated HK-2 cells were investigated. Moreover, luciferase reporter assay was performed to confirm the regulatory relationship between miR-23a-3p and wnt5a. Whether miR-23a-3p regulated the activation of Wnt/β-catenin signaling was also explored. mR-23a-3p was lowly expressed in the serum of patients with sepsis-associated AKI and in LPS-treated HK-2 cells. In addition, the overexpression of miR-23a-3p restrained LPS-induced proliferation inhibition and promotion of apoptosis and cytokine production in HK-2 cells. Moreover, wnt5a was identified as a target of miR-23a-3p, which could be negatively regulated by miR-23a-3p. Overexpression of miR-23a-3p suppressed the activation of Wnt/β-catenin signaling in LPS-treated HK-2 cells, which was markedly reversed by wnt5a upregulation. Upregulation of miR-23a-3p may alleviate LPS-induced cell injury by targeting wnt5a and inactivating Wnt/β-catenin pathway, which may serve as a novel therapeutic target for sepsis-associated AKI.